Pengaruh Motivasi Membaca dan Minat Membaca terhadap Hasil Belajar Tematik Peserta Didik - Deli Malisda; Muhammad Mona Adha; Roy Kembar Habibi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Lampung, 2023)
The problem in this study is the low thematic learning outcomes at grade v students of sd negeri 2 gedong air. This study aims to analyze and describe the effect of reading motivation and reading interest on students' thematic learning outcomes. This type of research is quantitative with an ex-post facto correlation research method. The sample in this study was all students in grades VA, VB, and VC, totaling 82 people. Data collection techniques using observations, questionnaires, and documents. The data collection instrument used was a likert scale questionnaire, which had been tested for validity and reliability. The data analysis used is a multiple linear regression test. The results showed that there was a positive and significant effect between reading motivation and reading interest on thematic learning outcomes of grade V students at SD Negeri 2 Gedong Air with a contribution of 61.77%. Reading motivation and interest in reading greatly impact thematic learning outcomes. High reading motivation will strengthen students' desire to acquire knowledge, high reading interest will have an impact on students' reading comprehension, thus impacting the learning outcomes obtained.